Physical exercise frequency and cognition: a multicenter cross-sectional cohort study - Wen, Chen; Gan, Jing-Huan; Huang, Guo-Wei; Wang, Xiao-Dan; Lü, Yang; Niu, Jian-Ping; Meng, Xin-Ling; Cai, Pan; Li, Yang; Gang, Bao-Zhi; You, Yong; Lv, Yan; et al. (Frontiers in Aging Neuroscience, 2024)
Background and aims Dementia imposes a heavy burden on society and families, therefore, effective drug treatments, exploring and preventing factors associated with dementia, are paramount. To provide reference points for the best frequency of physical exercise (physical exercise), we investigated the association between frequency of PE and cognition in Chinese old adults. Methods 16,181 Chinese participants aged 65 years or older were included in this study. Associations between PE and cognition were estimated multivariate logistic and linear regression analyses. Associations were further investigated across dementia subtypes (Alzheimer dementia, vascular dementia, and other types of dementia). Subgroup analyses were performed in different age groups, in populations with and without stroke, and those with and without hypertension. Results PE associated with dementia after adjusting for full covariates (OR: 0.5414, 95% CI: 0.4536–0.6491, p < 0.001). Exercise performed at ≥3 times/week associated with lower risk of dementia (OR: 0.4794–0.6619, all p value <0.001). PE was associated with improved cognition (β: 12851, p < 0.001), and any PE frequency contributed to cognitive improvement (p values for exercise performed ≥1 time/week were <0.001). Similar conclusions were identified when we repeated analyses in different dementia subtypes and age groups. Subgroup analyses suggested that the cognition of individuals without hypertension also benefitted from exercising 1–2 times/week (OR: 0.6168, 95% CI: 0.4379–0.8668, p = 0.005). Conclusion The best exercise frequency is exercising ≥3 times/week for individuals from different dementia subtypes and age groups. While for those without hypertension, PE at 1–2 times /week is also beneficial.